Varietal identification and fingerprinting of Pearl Millet (Pennisetum glaucum L.) varieties and hybrid using morphological descriptors and SSR markers - Natesan, Senthil; Kali, Subbulakshmi; Venkateswaran, Kaavya; Selvam, Keerthika; Krishnamoorthy, Iyanar; Rajasekaran, Ravikesavan; Geetha, S. (Current Botany, 2021)
Pearl Millet (Pennisetum glaucum) is the sixth most important cereal crop in the world. The genomic resources available in Pearl millet can be utilized for fingerprinting and screening of hybrids using SSR markers and will be helpful for the assessment of seed purity. Hence, the present study was focused on fingerprint popular pearl millet varieties and hybrids of Tamil Nadu for varietal identification and hybrid purity test. The varieties used for DNA fingerprinting were CO (Cu) 9, CO 10, Pearl Millet hybrid CO 9 along with the parents, A’ line ICMA 93111A and R’ line PT 6029-30. The morphological features were recorded to screen the cultivars. The Pearl millet hybrid CO 9 scored the highest value for more than four quantitative characters via., Number of productive tillers (4-6), Leaf blade length (60-68cm), Leaf blade width (4.0-4.5cm), number of nodes (8-10), and 1000 seed weight (13-14g) which is at par and comparable with the composite CO 10 and higher than that of the variety CO (Cu) 9. PCR was performed using 36 SSR primers to find out polymorphism among the varieties. The SSR markers ICMP3021 and PSMP2089 were able to selectively identify CO (Cu) 9 from the other varieties. Whereas, the SSR markers ICMP3018, PSMP2219, and PSMP2220 were used to distinguish CO 10 from the other varieties. Further, the CO10 variety produced additional alleles for all the markers due to its composite nature. Among the thirty-six SSR primers screened, none of them were found suitable to distinguish the TNAU hybrid CO 9 from its parents. The unique DNA fingerprints developed in the present study can be utilized for seed purity testing and varietal identification.